COMMUNITY PARTICIPATION IN DRIVING EMPOWERMENT THROUGH TOURISM DEVELOPMENT (Case Study on Wayang Windu Panenjoan Tourism Destinations) - Fajri, Muthia Yasmina; Shantini, Yanti; Akhyadi, Ade Sadikin (Indonesian Journal of Adult and Community Education, 2022)
A tourism development approach that emphasizes community involvement can run optimally in the tourism development process. Tourism is organized with the principle of empowering local communities covering various aspects, such as human resources, destinations, and the utilization of natural and cultural resources. This is inseparable from community participation in the development of Wayang Windu Panenjoan tourist destinations. This study aims to identify the level of community participation in the development of tourist destinations in Wayang Windu Panenjoan, analyze the form of community participation in the development of Wayang Windu Panenjoan tourist destinations, and review the extent of community empowerment in Wayang Windu Panenjoan tourist destinations. This study uses a qualitative method with a case study approach. The research was conducted at the Wayang Windu Panenjoan tourist destination on the people who participated in the development of the Wayang Windu Panenjoan tourist destination and the surrounding community who became respondents with a total of 8 people. The data collection technique is conducted by interview and observation. The steps of data analysis carried out in this study are data reduction, data presentation, and conclusion. From the research, it was found that the community has reached the top of the ladder in the level of participation, also beyond the stage of passive involvement to play a more active role. The community participates in the form of thoughts, energy, thoughts and energy, expertise, goods, and money, and participates in the form of decision making, implementation, receiving benefits, and evaluation. Community participation in the development of Wayang Windu Panenjoan tourism destinations can encourage people to become more empowered. Not only the people who participated became more empowered, but the people around Wayang Windu Panenjoan also felt a good impact on their survival.